Application of Science Process Skills in Courses of Basic Science Concepts - Istianah, Farida; Suryanti, Suryanti; Mintohari, Mintohari; Julianto, Julianto (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
The aim of this research is to determine the effect of applying the science process skills (KPS) approach to student learning outcomes in the Basic Concepts of Science course. This research uses a quantitative approach with a one group pre-test post-test design. Data collection is carried out by observation, tests and documentation. Primary data sources are obtained from learning outcomes and student responses regarding the implementation of learning using a process skills approach. Meanwhile, secondary data is based on literature and previous research related to science process skills. Data analysis was carried out using the normality test, paired sample t test and N-Gain test. The population in this study were students of the 2023 class of the Primary School Teacher Education Study Program, Surabaya State University. Using a random sample from class B with a total of 43 students. The research results showed that the average pre-test score was 68.76, then after applying science process skills the average post-test score was 84.27, which shows effectiveness in increasing students' understanding of basic science concepts courses. This is supported by N-Gain data which produces an increase of 0.60 in the moderate increase category.